2000
DOI: 10.1074/jbc.m005967200
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Methionine Biosynthesis fromS-Adenosylmethionine in Eukaryotic Cells

Abstract: The intracellular ratio between methionine and its activated form S-adenosylmethionine (AdoMet) is of crucial importance for the one-carbon metabolism. AdoMet recycling into methionine was believed to be largely achieved through the methyl and the thiomethyladenosine cycles. We show here that in yeast, AdoMet recycling actually occurs mainly through the direct AdoMet-dependent remethylation of homocysteine. Compelling evidences supporting this result were obtained owing to the identification and functional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…The isa mutants are not impaired in desthiobiotin uptake, as was evident from the fact that their biotin-dependent enzymes were desthiobiotinylated in the absence of biotin. In addition, these cells must be capable of producing SAM, as this is an essential metabolite (58). Sulfur is most likely derived from cysteine and transferred via one of the two Fe/S clusters of biotin synthase (59).…”
Section: Discussionmentioning
confidence: 99%
“…The isa mutants are not impaired in desthiobiotin uptake, as was evident from the fact that their biotin-dependent enzymes were desthiobiotinylated in the absence of biotin. In addition, these cells must be capable of producing SAM, as this is an essential metabolite (58). Sulfur is most likely derived from cysteine and transferred via one of the two Fe/S clusters of biotin synthase (59).…”
Section: Discussionmentioning
confidence: 99%
“…Six of them are among the eight target genes of the Cbf1-Met4-Met28 transcription complex mediating the repression of transcription in response to methionine (124), and the two others are also known to be repressed by methionine (52,123). The two remaining Cbf1-Met4-Met28 target genes (MET10 and MET2) are also expressed to a lower level on methionine medium in our study but are not among the 506 genes displaying significant variation of expression on one or more tested nitrogen sources from that on urea.…”
mentioning
confidence: 99%
“…Previous studies have shown that there are at least two homocysteine methyltransferase enzymes present in Saccharomyces cerevisiae (28,29). These are encoded by the SAM4 and MHT1 genes and utilize AdoMet and S-methylmethionine, respectively, as methyl donors (29). It is not clear whether either of these enzymes was responsible for the utilization of (R,S)-AdoMet seen initially (23).…”
mentioning
confidence: 80%
“…In this work, homocysteine methyltransferase activity was observed at twice the rate when an S,S/R,S mixture of AdoMet was used compared with that seen with the S,S form at an equal total concentration (23). Previous studies have shown that there are at least two homocysteine methyltransferase enzymes present in Saccharomyces cerevisiae (28,29). These are encoded by the SAM4 and MHT1 genes and utilize AdoMet and S-methylmethionine, respectively, as methyl donors (29).…”
mentioning
confidence: 97%